Ypt1 and COPII vesicles act in autophagosome biogenesis and the early secretory pathway. (26th January 2015) - Davis, Saralin; Ferro-Novick, Susan
Abstract : The GTPase Ypt1, Rab1 in mammals functions on multiple intracellular trafficking pathways. Ypt1 has an established role on the early secretory pathway in targeting coat protein complex II (COPII) coated vesicles to the cis -Golgi. Additionally, Ypt1 functions during the initial stages of macroautophagy, a process of cellular degradation induced during periods of cell stress. In the present study, we discuss the role of Ypt1 and other secretory machinery during macroautophagy, highlighting commonalities between these two pathways.